2006
DOI: 10.1248/cpb.54.779
|View full text |Cite
|
Sign up to set email alerts
|

New C19-Diterpenoid Alkaloids from Aconitum piepunense

Abstract: The plant Aconitum piepunense HAND-MAZZ. Symb. Sin. grows in Diqing county, Yunnan province, China at an elevation of 3000 m.1) To our knowledge, no phytochemical investigation of this plant has been undertaken. In the course of our continued studies of diterpenoid alkaloids from Aconitum and Delphinium plants, two new C 19 -diterpenoid alkaloids, piepunensine A (1) and 18-acetylcammaconine (2), along with five known norditerpenoids pengshenine B (3), talatisamine (4), aconosine (5), yunaconitine (6), and tala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…
In the course of comparative research of new activities of alkaloids and evaluation of chemotaxonomy of the diterpenoid alkaloids from the Aconitum and Delphinium species, [1][2][3] we investigated the alkaloids of D. anthriscifolium var. savatieri (FRANCHET) MUNZ.
…”
mentioning
confidence: 99%
“…
In the course of comparative research of new activities of alkaloids and evaluation of chemotaxonomy of the diterpenoid alkaloids from the Aconitum and Delphinium species, [1][2][3] we investigated the alkaloids of D. anthriscifolium var. savatieri (FRANCHET) MUNZ.
…”
mentioning
confidence: 99%
“…The IR spectrum indicated the absorption peaks for a carbonyl group (1710 cm −1 ), and aromatic ring (1609, 1592, 1515, 1452 cm −1 ). The NMR spectrum of 1 exhibited characteristic features of the aconitine-type C 19 -diterpenoid alkaloids, [10][11][12][13][14][15] bearing an N-ethyl group (δ H 1.01, 3H, t, J = 7.2 Hz; δ C 13.6 q, 49.3 t), and two methoxy groups (δ H 3.19, 3.32, each 3H, s; δ C 56.2 q, 56.4 q). Furthermore, the signals at δ Comparison of the MS and NMR spectra of 1 with those of the known brevicanine A 17) showed that these two compounds exhibited nearly identical 1 H-and 13 C-NMR resonances.…”
Section: Resultsmentioning
confidence: 99%
“…The NMR spectrum of 1 exhibited characteristic features of the aconitine-type C 19 -diterpenoid alkaloids, [10][11][12][13][14][15] bearing an N-ethyl group (δ H 1.01, 3H, t, J = 7.2 Hz; δ C 13.6 q, 49.3 t), and two methoxy groups (δ H 3.19, 3.32, each 3H, s; δ C 56.2 q, 56.4 q). Furthermore, the signals at δ Comparison of the MS and NMR spectra of 1 with those of the known brevicanine A 17) showed that these two compounds exhibited nearly identical 1 H-and 13 C-NMR resonances. The most obvious difference between compounds 1 and brevicanine A in their NMR spectra was the absence of a methoxy group in 1, thus validating the loss of 14 mass units in brevicanine A as found by mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…文献数据也支持这一判断, 若在 C-8 上形成碳碳 键则 C-6 的化学位移应该在 δ 100 左右 [6] , 若在 C-6 上形 成碳碳键则 C-8 的化学位移在 δ 95 左右 [7] , 而该化合物 中 A 环上的芳香 CH 的化学位移是 δ C 94.58, 由此进一 步确定该 CH 2 与 C-6 形成碳碳键. 仔细分析 1 的 NMR 数据, 发现该化合物中还含有 1 个甲氧基[δ 糖基异头氢的偶合常数为 7.2 Hz [8] , 通过水解测得 的旋光值为 20 [9] ; 对香豆酸酯基的 2 个双键氢的偶合常数 为 15.9 Hz [10] , [12] , HMBC 谱中存在的 δ H 5.18 (H-7)与 δ C 168.7…”
unclassified